Preliminary overview of the economies of Latin America and the Caribbean.... -2005- (UN ECLAC SantiagoCL)
This publication appears at the end of each year. It contains a description and asessment of the economic performance of the region during the year and provides updated, detailed information about the evolution of macroeconomic variables in the region as an aggregate and in most individual countries. It stands as the earliest source of information on the region's economic performance for the entire year. The reports includes a Regional Panorama based on a global and sectoral approach; growth projections for the following year are included. Additionally, individual country chapters cover the economies in Latin American and a the Caribbean. This document is prepared by the Economic Development Division in collaboration with the Statistics Division and the subregional and national offices of the ECLAC.
Documentation Centre has: 2005-2020